Optimization of N-benzyl-benzoxazol-2-ones as receptor antagonists of macrophage migration inhibitory factor (MIF) - Hare, Alissa A. (2010)
The cytokine MIF is involved in inflammation and cell proliferation via pathways initiated by its binding to the transmembrane receptor CD74. MIF also exhibits keto-enol tautomerase activity, believed to be vestigial in mammals. Starting from a 1-μM hit from virtual screening, substituted benzoxazol-2-ones have been discovered as antagonists with IC(50) values as low as 7.5 nM in a tautomerase assay and 80 nM in a MIF-CD74 binding assay. Additional studies for one of the potent inhibitors demonstrated that it is not a covalent inhibitor of MIF and that it attenuates MIF-dependent ERK1/2 phosphorylation in human synovial fibroblasts.